(untitled) (Ustozlar uchun, 2026)
The assessment of urban bus service regularity is usually based on a simple ratio between the number of trips operated within the permissible deviation and the total number of planned trips. Although this indicator is convenient, it does not reflect the full operational picture because it ignores the magnitude of headway deviations, travel time instability, and the presence of missed trips. As a result, routes with different operational quality may receive similar regularity scores. This paper develops an improved integral coefficient model for evaluating the regularity of urban bus routes. The proposed model combines four components: the basic regularity coefficient, the headway stability coefficient, the travel time stability coefficient, and the trip completion coefficient. Each component is normalized and included in a weighted integral index. A computational experiment was carried out for five urban bus routes. The results showed that the traditional regularity coefficient alone overestimates the quality of some routes, whereas the integral coefficient gives a more balanced and realistic assessment. For example, one of the studied routes had a basic regularity level of 89,0%, but its integral regularity score was only 84,4% because of significant headway and travel time instability. The proposed model can be used in route monitoring, comparative performance analysis, dispatch diagnostics, and transport planning.